Analysis and design of constant-frequency peak-current-controlled high-power-factor boost rectifier with slope compensation - Canesin, Carlos A. [UNESP]; Barbi, Ivo [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1996)
This paper presents the analysis and the design of a peak-current-controlled high-power-factor boost rectifier, with slope compensation, operating at constant frequency. The input current shaping is achieved, with continuous inductor current mode, with no multiplier to generate a current reference. The resulting overall circuitry is very simple, in comparison with the average-current-controlled boost rectifier. Experimental results are presented, taken from a laboratory prototype rated at 370 W and operating at 67 kHz. The measured power factor was 0.99, with a input current THD equal to 5.6%, for an input voltage THD equal to 2.26%.
Keywords: Electric current control; Electric power factor; Electric power factor correction; Power supply circuits; Continuous inductor current mode; High power factor boost rectifier; Input current shaping; Slope compensation; Electric rectifiers